2020
DOI: 10.3390/foods9091193
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Fermentation Water Addition to High-Sugar Shiraz Must: Effects on Wine Composition and Sensory Properties

Abstract: Changes to Australian regulations now allow the limited addition of water to high-sugar musts pre-fermentation. In light of these changes, this study explored how water addition affects Shiraz wine composition and sensory properties. Wines were made from grapes at ≈13.5, 14.5 and 15.5° Baume. Water was added to musts from the ripest fruit by direct addition, or by using a juice substitution (run-off and replace) approach. To compare the effect of juice run-off independently, saigneé treatments were included. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…Wine colour density, tannin, phenolic substances and total anthocyanin concentration have been identified previously as predictors for the ‘opacity’ attribute (Bindon et al 2019). Whereas 2‐phenylethyl acetate has been shown to correlate positively with ‘red fruit’ aroma and negatively with ‘dark fruit’ character (Teng et al 2020). In Cabernet Sauvignon wines, ester concentration and dimethyl sulfide have been found to predict the ‘dark fruit’ attribute (Bindon et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Wine colour density, tannin, phenolic substances and total anthocyanin concentration have been identified previously as predictors for the ‘opacity’ attribute (Bindon et al 2019). Whereas 2‐phenylethyl acetate has been shown to correlate positively with ‘red fruit’ aroma and negatively with ‘dark fruit’ character (Teng et al 2020). In Cabernet Sauvignon wines, ester concentration and dimethyl sulfide have been found to predict the ‘dark fruit’ attribute (Bindon et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…• Brix showed a reduction in alcohol content with similar sensory results as wine obtained from early grape harvest [68]. However, higher levels of water addition may reduce must acidity, lower the concentrations of phenolics and tannins, and have a negative impact on wine appearance and sensory attributes [63,[69][70][71].…”
Section: Dilution/blending Of Grape Mustmentioning
confidence: 61%
“…Though, in some countries such as the United States (excluding California), water can be added in very small amounts as a processing aid to achieve the desired result, this act is illegal and restricted in most other countries like South Africa, New Zealand, Austrilia, France, and Germany [27,72]. Some studies have reported good results from adding water to grape must to reduce wine alcohol content [61][62][63]67,68,70,71]. For example, Schelezki et al [62] investigated the pre-fermentative substitution of Cabernet Sauvignon grape must (30.4 • Brix) with either "green harvest wine" of 4.5% ABV or water in the production of lower alcohol wines.…”
Section: Dilution/blending Of Grape Mustmentioning
confidence: 99%
“…When 14% of juice was removed from the must at crushing, the total anthocyanins content in Cabernet Sauvignon wine increased by ~ 10% and showed more red hue than the control [ 24 ]. However, in Shiraz wines, the content of total anthocyanins was not significantly different between saignée and control, no matter the amount of juice removed (8% or 17%), while the 17% juice removal showed significantly higher non-bleachable pigment and polymeric pigment content than the 8% juice removal and control [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Since most of polyphenols accumulate in the grape skins, removing the juice with certain level or ratio would theoretically increase the concentration of water-soluble compounds in the juice. Most research on Vitis vinifera red wines revealed that saignée treatment led to more red hue and higher phenolic compounds extraction in different varieties, such as Cabernet Sauvignon [ 24 , 25 ], Shiraz [ 26 , 27 ], and Monastrell [ 28 ]. Considering the correlation between the quality and the concentration of phenolics in the finished wine, more pronounced effects of the saignée treatment on color stability and phenolic compounds extraction were observed with the increase in the juice run-off percentage [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%